Dukungan Keluarga Dan Sosial Budaya Dengan Risiko Anemia Pada Ibu Hamil - Hairuddin K; Jumrah Sudirman; Suriani B (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Based on anemia data obtained from the results of medical records at the Lepo-lepo Health Center in Kendari, 128 (11.07%) pregnant women experienced anemia from 1,156 patients who checked their pregnancy in 2013, there were 112 (6.68%) pregnant women who experienced anemia from 1,675 patients checked their pregnancy, and in 2014 was 97 (5.48%) pregnant women had anemia from 1,768 patients who checked their pregnancy. This study aimed to analyze the sociocultural relations and family support with the incidence of anemia in pregnant women. The research method used was analytic observational with a Cross-Sectional Study approach. The total sample was 33 pregnant women with a purposive sampling technique. The study found that most pregnant women still experienced anemia due to a lack of family support. The amount of family support a mother receives affects the anemia of pregnant women. This effect can interfere with the psychological health of pregnant women, such as experiencing stress. For the mother to feel calm and at ease during pregnancy, it is hoped that the pregnant woman's family can provide full support so that there is a sociocultural relationship and family support with the incidence of anemia in pregnant women with each value ρ <α (0.05). It can be concluded that there is a relationship between sociocultural and family support with the incidence of anemia in pregnant women. As a recommendation in research to improve sociocultural relationships and family support with the incidence of anemia in pregnant women